Hello ! Pls solve the following. Thank you. No spamming.
Attachments:
![](https://hi-static.z-dn.net/files/d17/a4014534d3812731b95abb97f1561acb.jpg)
Answers
Answered by
1
Answer:
hey here is your answer
pls mark it as brainliest
Step-by-step explanation:
so let the two numbers be x and y
so here x+y=-4/3 (1)
also x=1 (2)
substituting value of x in (1)
we get
x+y=-4/3
so y=-4/3-x
=-4/3-1
-4-3/3
=-7/3
thus y=-7/3
hence the other number is -7/3
Answered by
8
let other no. = X
x+ -4/3=1
X= -4/3-1
X = (-4-1)/3
X = 5/3
other no. = 5/3
⫷Here is your answer⫸
꧁XxMissHeartHackerxX꧂
Similar questions